Ectopic primary olfactory neuroesthesioblastoma originating from the anterior nasal septum - Lim, Sin Wee; Mohamad, Wan Emelda Wan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Olfactory neuroestesioblastoma (ONB) is a rare malignant neoplasm of the paranasal sinus. Ectopic growth of ONB outside the region of neuroepithelial cells are exceedingly rare and so far, it has only been reported to arise from the maxillary sinus, sphenoid sinus, posterior septum and the turbinates. None has been reported to originate from the anterior cartilaginous part of the septum. A 31-year-old lady, who was premorbidly well, presented with 2 episodes of spontaneous epistaxis from the left nostril in 1 year. The epistaxis worsened over the one week prior to her visit. Nasoendoscopy showed a vascularised round mass at the anterior part of the left septum. Initial biopsy was reported as possible ectopic squamous cell carcinoma of the salivary gland. A repeat biopsy then confirmed the diagnosis of ONB. Computed tomography scan of the paranasal sinus showed an isolated mass (18×18 mm) arising from the anterior part of the septum. Endoscopic resection of the tumour was done and histopathology report revealed as ONB. Post-operative radiotherapy was given with a total dose of 66. The rarity of ONB poses a challenge during diagnosis. The histological identification is difficult as these tumours may show little or no differentiation. A simple biopsy from the mass is often insufficient and may produce inaccurate results. Isolated growth without involvement of the upper nasal vault is extremely rare. A possible explanation would be the presence of ectopic neuroepithelial cells at the cartilaginous anterior septal area that has failed to degenerate during fetal development.